Nutrition Training for Madrasah Ibtidaiyah Teachers in Semarang Regency - Widajanti, Laksmi; Qothrunnada, Alisa; Hidayah, Aisyah Nurul (Jurnal Gizi dan Pangan, 2023)
The purpose of this study was to analyze the knowledge of Madrasah Ibtidaiyah (MI) teachers in Semarang Regency about nutrition. This study used a quasi-experimental design. Seventeen teachers were provided with training covering four modules in four hours. The data obtained were analyzed using ANOVA. It showed that the understanding of 94% of the teachers about nutrition had a score higher than 60. There was a slight increase in the knowledge of nutrition among the teachers but it was not statistically significant (F=2.395; p=0.173). It is concluded that training on nutrition for MI teachers in Semarang Regency slightly increased their knowledge on nutrition.